Effect of the FIFA 11+ injury prevention program in collegiate female football players over three consecutive seasons - Magoshi, H.; Hoshiba, T.; Tohyama, M.; Hirose, N.; Fukubayashi, T. (Scandinavian Journal of Medicine & Science in Sports, 2023)
This study aimed to investigate the preventive effects of the FIFA 11+ for one-season and over three consecutive seasons on the injury incidence rates in collegiate female football players in terms of duration of intervention. A total of 763 collegiate female football players from seven teams belonging to Kanto University Women Football Association Division 1 in 2013-2015 seasons were included in the study. At the start of the study, 235 players were assigned to a FIFA 11+ intervention group (four teams, 115 players) and a control group (three teams, 120 players). The intervention period was set to three seasons, and the players were followed up during this period. The one-season effect of the FIFA 11+ was investigated after each season. The effect of continuous intervention was verified in 66 and 62 players from the intervention and control groups who continued the study for all three seasons, respectively. The one-season intervention showed significantly lower total, ankle, knee, sprain, ligament injury, noncontact, moderate and severe injury incidence rates in the intervention group in each season. Regarding the continuous intervention, compared with the first season, the injury incidence rates in lower extremity, ankle, and sprain, decreased in the intervention group by 66.0%, 79.8%, and 82.2%, respectively, in the second season, and by 82.6%, 94.6%, and 93.4%, respectively, in the third season, indicating the persistent effect of the FIFA 11+. In conclusion, the FIFA 11+ is an effective program for lower extremity injury prevention in collegiate female football players, and preventive effects persist with continuation of the program.